1998
DOI: 10.1007/s004240050550
|View full text |Cite
|
Sign up to set email alerts
|

Proton inhibition of GABA-activated current in rat primary sensory neurons

Abstract: The modulation of the Cl- current activated by gamma-aminobutyric acid (GABA) by changes in extracellular pH in freshly isolated rat dorsal root ganglia (DRG) neurons was studied using the whole-cell patch-clamp technique. In the pH range of 5.0-9.0, increased extracellular pH enhanced, and decreased extracellular pH suppressed, current activated by 10 microM GABA in a reversible and concentration-dependent manner with an IC50 of pH 7.1 in these neurons. Acidification to pH 6.5 inhibited currents activated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
7
25
0
Order By: Relevance
“…Variations in the level of endogenous ions in the CNS represent a rapid and effective method for regulating receptor function (Kaila, 1994;Smart et al, 1994). Previous studies have indicated that protons can differentially affect neuronal GABA A receptors, resulting in potentiation, inhibition, or no effect on GABA-activated responses (Kaila, 1994;Robello et al, 1994;Pasternack et al, 1996;Zhai et al, 1998;Krishek and Smart, 2001). This variability to pH has been ascribed to differences in the neuronal receptor subunit composition that can be reproduced to some extent using recombinant GABA A receptors .…”
Section: Abstract: Gaba a Receptor; Ph Modulation; ␤ Subunit; Histidmentioning
confidence: 99%
“…Variations in the level of endogenous ions in the CNS represent a rapid and effective method for regulating receptor function (Kaila, 1994;Smart et al, 1994). Previous studies have indicated that protons can differentially affect neuronal GABA A receptors, resulting in potentiation, inhibition, or no effect on GABA-activated responses (Kaila, 1994;Robello et al, 1994;Pasternack et al, 1996;Zhai et al, 1998;Krishek and Smart, 2001). This variability to pH has been ascribed to differences in the neuronal receptor subunit composition that can be reproduced to some extent using recombinant GABA A receptors .…”
Section: Abstract: Gaba a Receptor; Ph Modulation; ␤ Subunit; Histidmentioning
confidence: 99%
“…Protons also neutralize negative surface charge, shifting the voltage-dependence of Ca 2+ channels to more positive potentials [97,98] . Various studies have indicated that protons can affect neuronal GABA A receptors differently depending on the receptor subunit composition, resulting in potentiation, inhibition, or no effect on GABA-induced responses [12,57,[102][103][104][105][106] (Fig. 1).…”
Section: Vgccs Synaptic Vesicles Are Always Acidified Bymentioning
confidence: 99%
“…These findings suggest that protons modulate the desensitization of GABA A receptors in a subunit-dependent manner. A reduction in extracellular pH has been reported to either have no influence on desensitization (Pasternack et al 1996;Robello et al 1994) or decrease desensitization (Mozrzymas et al 2003;Zhai et al 1998) of GABA A receptors on native neurons. These inconsistent data may be due to the presence of multiple population of GABA A receptor isoforms on these neurons.…”
Section: Incorporation Of a ␥2l Or A ␦ Subunit Into ␣1␤3 Receptors Almentioning
confidence: 99%
“…However, it was reported that exposure of the HEK cells to Krebs solution at pH 5.4 for minutes induced negligible alterations of intracellular pH (Krishek et al 1996). In addition, limited acidification of the intracellular environment may not affect GABA A receptor function (Pasternack et al 1992;Zhai et al 1998). Therefore we interpreted the 28-s application data in the same FIG. 4.…”
Section: Reduction Of Ph Enhanced Steady-state Currents Of ␣1␤3␦ Recementioning
confidence: 99%
See 1 more Smart Citation